Non-destructive detection of jelly seed disorder in Amrapali and Pusa Surya varieties of mango (Mangifera indica) - KRISHNA, K RAMA; SHARMA, R R; KAR, A; SRIVASTAV, M (The Indian Journal of Agricultural Sciences, 2019)
Mango (Mangifera indica L.) varieties, viz Amrapali and Pusa Surya were subjected to X-ray imaging for detection of jelly seed disorder. Fruits of each variety were subjected to X-rays with different combinations of voltage, current and time in a trial and error manner to obtain X-ray image. It was found that X-ray source of 48 kV, 6.5 mA, with an exposure time of 320 mA gave the best contrast images of jelly seed internal disorder. X-ray images were stored and further processed with MATLAB. Fruits which were used for X-ray imaging were also compared destructively for jelly seed disorder incidence. After comparison, it was found that both destructive and non-destructive (X-ray) images, as well as processed images, were similar. Hence, it can be concluded that X-ray imaging can be an useful method for detecting jelly seed disorder in mango.